Safe care management of children with milk allergy: the student's health and its perspectives (Research, Society and Development, 2020)
This article presents the results from an integrative revision of the national and international literature on existing safety actions for managing the care for students with cow’s milk allergy (CMPA). Thirty-four articles published between 2013 and 2019 were analyzed from the selection in the databases BVS and PubMed. Many of them indicated that the school nurse is the ideal healthcare professional to manage risk prevention and develop Individual Plans and Emergency Plans in schools. Self-injectable epinephrine was mentioned as the first-line treatment for anaphylaxis. This study established five goals for safety of students with CMPA, from the correlation of safety actions indicated in publications with the International Patient Safety Goals promoted by the World Health Organization (WHO)